In Vitro Treatment with 2‐APB Inhibits the Inflammation in Nasal Polyps. (17th June 2015) - Lin, Lin; Dai, Fei; Chen, Zhongchun; Cai, Lihui
Abstract : Objective: Glucocorticoids are considered the main treatment option for chronic rhinosinusitis with nasal polyps (CRSwNP), but their effect rate ranges from 60.9% to 80%. Novel therapeutic means should be studied. The purpose of this study was to investigate the expression of Orai1 in nasal polyps (NPs) and the influence of intervention of Orai1 on NPs after in vitro treatment of 2‐aminoethoxydiphenyl borate (2‐APB). Study Design: Prospective cross‐sectional study. Setting: University hospital. Subjects and Methods: Nasal biopsy samples were obtained from normal subjects or subjects with CRSwNP. We studied the localization of Orai1 protein in NPs by using immunohistochemistry. Then these tissues in cultures were maintained in the absence or presence of dexamethasone (DEX) or 2‐APB. Orai1 was examined by Western blot, enzyme‐linked immunosorbent assay (ELISA), and real‐time reverse transcription‐polymerase chain reaction (RT‐PCR). Inflammatory mediators including interleukin (IL)‐1β, IL‐5, eosinophil cation protein (ECP), leukotriene (LT)C4, interferon (IFN)‐γ, and dermatophagoides pteronyssinus (DP)‐specific immunoglobulin E (sIgE) as well as mucins (MUCs) including MUC5B and MUC7 in cultures were analyzed with ELISA and real‐time RT‐PCR. Results: The expression of Orai1 was localized to cytoplasmic membrane of inflammatory cells and submucosal glandular cells and was upregulated in NPs compared with normal nasal mucosa. Orai1 was decreased in NPs after in vitro treatment of 2‐APB but not after DEX intervention. The levels of inflammatory mediators and mucins were reduced more after 2‐APB treatment when compared with those after DEX treatment. Conclusion: Orai1 may play crucial roles in NP formation, and the intervention of Orai1 may inhibit NP development.